A Synectic Model Based on Literature Ecocritic in Poetry Writing Learning - Henanggil, Mita Domi Fella; Idris, Mohd. Rashid Md; Rasyid, Yulianti; Hayati, Yenni (Language Pedagogy Study Program, Faculty of Languages and Arts, Universitas Negeri Padang, Indonesia, 2022)
The synectic model is the basis for increasing creativity. The synectic model in learning to write poetry is one of the right steps to research. Creativity is the basis for writing activities. Writing activities require high creativity in producing good and original writing. The ability to write is always a problem from time to time because bringing out the creativity that exists in a person is not easy, but a way is needed to foster that creativity. One of the steps is to use the synectic model in learning to write poetry. The synectic model that carries steps to think creatively on the basis of metaphors helps students grow their creativity in writing poetry. The synectic model in learning to write poetry is then juxtaposed with literary ecocriticism, the goal is to produce literary works that care about the surrounding environment. Submission of criticism of the environment in the form of poetry will make an interesting work. This type of research is quantitative with a quasi-experimental method using a control class and an experimental class.